1998
DOI: 10.1055/s-0037-1615089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a once Daily with a twice Daily Subcutaneous Low Molecular Weight Heparin Regimen in the Treatment of Deep Vein Thrombosis

Abstract: SummaryBackground: Clinical trials have been performed to compare with standard heparin a once or a twice daily regimen of low-molecular-weight heparin but no direct comparison has been done between these two low-molecular-weight heparin regimens in terms of efficacy and safety with a long-term clinical evaluation.Methods: Patients with proximal deep vein thrombosis, confirmed by venography were randomly assigned to either nadroparin (10,250 AXa IU/ml) twice daily or nadroparin (20,500 AXa IU/ml) once daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 17 publications
0
32
0
3
Order By: Relevance
“…I Because of their greater bioavailability, low-molecular-weight heparins can be administered subcutaneously without the need for laboratory monitoring. Randomized, controlled trials of treatment for acute deep-vein thrombosis [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or pulmonary embolism 21 have demonstrated that low-molecular-weight heparins are at least as effective and safe as unfractionated heparin. In addition to the assessments of clinical outcome, repeated venography has revealed a tendency for the thrombus to regress in the groups receiving a low-molecular-weight heparin.…”
mentioning
confidence: 99%
“…I Because of their greater bioavailability, low-molecular-weight heparins can be administered subcutaneously without the need for laboratory monitoring. Randomized, controlled trials of treatment for acute deep-vein thrombosis [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or pulmonary embolism 21 have demonstrated that low-molecular-weight heparins are at least as effective and safe as unfractionated heparin. In addition to the assessments of clinical outcome, repeated venography has revealed a tendency for the thrombus to regress in the groups receiving a low-molecular-weight heparin.…”
mentioning
confidence: 99%
“…gave higher rates of bleeding complications as compared with o.d. (relative risk, 1.64; 95% CI, 0.74–3.57) . When combining results from our study and the latter study in a post hoc meta‐analysis with a random effects model, the OR of the meta‐analysis indicates a 1.77 increased risk (95% CI, 0.97–3.23) for patients using b.i.d.…”
Section: Discussionmentioning
confidence: 67%
“…Once daily dosing is attractive because it may be more acceptable to the patient and involves less nursing time. In one controlled study [20], once daily nadroparin was shown to have equal efficacy and safety as twice daily nadroparin. The primary end-point of a combination of venous thromboembolism and mortality was reported in 13 patients (4.1%) in the group that received daily nadroparin and in 24 patients (7.2%) who received twice daily nadroparin.…”
Section: Randomized Trial Datamentioning
confidence: 99%